The klipfish code - Casanova, Mary. (Boston : Houghton Mifflin Co., 2007)
Sent with her younger brother to Gody̜ Island to live with her aunt and grandfather after Germans bomb Norway in 1940, ten-year-old Merit longs to join her parents in the Resistance and when her aunt, a teacher, is taken away two years later, she resents even more the Nazis' presence and her grandfather's refusal to oppose them. Includes historical facts and glossary.
Includes bibliographical references.
Accelerated Reader AR
Keywords: Patriotism -- Fiction; Family life -- Norway -- Fiction; Refugees -- Fiction; World War, 1939-1945 -- Underground movements -- Norway -- Fiction; Norway -- History -- German occupation, 1940-1945 -- Juvenile fiction; Norway -- History -- German occupation, 1940-1945 -- Fiction